Biventricular Thrombi in a Patient With Dilated Cardiomyopathy - Saba Mohammadzadeh; Afsaneh Amiri; Ali Hosseinsabet (Clinical Case Reports)
ABSTRACT In patients with dilated cardiomyopathy, it is important to thoroughly examine the right ventricle for the presence of a thrombus during transthoracic echocardiography, in addition to the left ventricle, especially when left ventricular thrombosis is present.